Renoprotective Effect of Desloratadine on Streptozotocin-induced Diabetic Nephropathy in Adult Male Long-Evans Rats (Mugda Medical College Journal, 2026)
Diabetic nephropathy (DN) is a leading cause of end-stage renal disease (ESRD) worldwide and a major microvascular complication of diabetes mellitus (DM). Despite current treatments, particularly those targeting the renin–angiotensin system, the progression of DN remains inadequately controlled. Histamine H1 receptors have emerged as potential contributors to glomerular dysfunction, mediating inflammation and oxidative stress in diabetic kidneys. Desloratadine, a potent H1 receptor antagonist, exhibits anti-inflammatory and antioxidant properties, suggesting its therapeutic potential in DN. This experimental, randomized controlled study aimed to evaluate the renoprotective effects of desloratadine in streptozotocin (STZ)-induced DN in adult male Long-Evans rats. Seventy adult male rats were divided into eight groups. Group I served as a blank control, and Group II received vehicle for STZ. Groups III–VIII were rendered diabetic via a single intraperitoneal injection of STZ (50 mg/ kg). Groups III, V, and VII served as diabetic controls, while Groups IV, VI, and VIII received daily oral desloratadine (10 mg/kg) for varying durations, initiated at different stages of DN progression. Serum creatinine was measured as a marker of renal function. Renal oxidative stress were assessed by malondialdehyde (MDA), reduced glutathione (GSH), and histopathological changes in renal tissue were also evaluated. In diabetic control groups, serum creatinine, and MDA levels were significantly elevated (p